2018
DOI: 10.1155/2018/1635635
|View full text |Cite
|
Sign up to set email alerts
|

Benign Scrotal Tumor in a Pediatric Patient: Epididymal Cyst

Abstract: A pediatric patient of 12 years consulted for a left scrotal mass of 2 months of evolution. After suspecting a cystic content due to positive transillumination, on ultrasonography a scrotal cyst separated from the testis, of 5 cm in its maximum length, was confirmed. Due to size, parental anxiety, and the referred short evolution, excision was decided. Given the clinical radiological findings, a scrotal incision was chosen, obtaining complete excision. Biopsy confirmed the diagnosis of simple epididymal cyst (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…Epididymal cysts are unilocular or multilocular collection of fluid in the epididymis as a result of dilatation of efferent epididymal tubules due to tubular obstruction. 1,2 A study found that local production of proinflammatory cytokines evidenced by elevated concentrations of interleukin 8 (IL-8), interleukin 6 (IL-6) in epididymal cyst is responsible for cyst formation. 4 They usually develop in adult men and mostly unilateral.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Epididymal cysts are unilocular or multilocular collection of fluid in the epididymis as a result of dilatation of efferent epididymal tubules due to tubular obstruction. 1,2 A study found that local production of proinflammatory cytokines evidenced by elevated concentrations of interleukin 8 (IL-8), interleukin 6 (IL-6) in epididymal cyst is responsible for cyst formation. 4 They usually develop in adult men and mostly unilateral.…”
Section: Discussionmentioning
confidence: 99%
“…Conservative management has been suggested in most cases although there is no consensus about the most adequate therapy of pubertal patients and the majority of these cysts involute with time 5 . The average time to complete involution varies from 4 to 50 months 2 . A study by BK Arora et al, reported that no spontaneous resolution was observed in the group of patients with cysts between 21 and 50 mm over a 1‐year follow‐up period 1 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is done with help of ultrasound and ethanol is inserted into cyst to kill the cells of cyst through catheter. Third option is excision/ removal of cyst which has least disadvantages [6].…”
Section: Introductionmentioning
confidence: 99%